EZH2 as a Regulator of CD8+ T Cell Fate and Function - Stairiker, Christopher J.; Thomas, Graham D.; Salek-Ardakani, Shahram (Frontiers in Immunology, 2020)
Enhancer of zeste 2 (EZH2) is the catalytic subunit of the Polycomb Repressive Complex 2 (PRC2) that mediates di- and trimethylation of histone 3 lysine 27 effectively precluding successful gene transcription at these loci. This class of epigenetic modifications facilitates the maintenance of tissue-specific cellular transcriptional programs as cells undergoing successive rounds of proliferation. CD8+ T cells are effective mediators of adaptive immunity and function to eliminate virus- and bacteria-infected cells as well as tumor cells. Upon recognition of cognate antigen, T cells undergo activation/proliferation to clear the target cells. The heterogeneous population of responding T cells formed during these proliferative events thus rely on epigenetic modifications to ensure identity and confer functional capabilities. In this review, we will focus on the role of the dynamic expression EZH2 in shaping the epigenetic landscape of CD8+ T cell fate and function, with a particular emphasis on infection and cancer. We also explore competing hypotheses pertaining to EZH2 function and the prospects of clinical EZH2 inhibitors in fine-tuning T cell responses.